Analysis of the Effectiveness of Conditional Release for Prisoners in the Class II B Garut Correctional Institution - Erwin Maulana Fashya; Zainudin Hasan (Jurnal Terekam Jejak, 2024)
This study evaluates the effectiveness of parole in alleviating prison overcrowding and enhancing inmate rehabilitation at Lembaga Pemasyarakatan Kelas II B Garut, addressing the urgent need for improved reintegration processes. The research employs a mixed-methods approach, combining descriptive analysis of questionnaires completed by parolees with semi-structured interviews of inmates, prison staff, and families. Findings indicate that most parolees, aged 26-35 years, struggle with social stigma and employment post-release, despite receiving parole. Only 40% felt ready to reintegrate, and support from rehabilitation programs varied widely, with only 40% feeling adequately supported. Counseling services were deemed beneficial by 55% of respondents. Challenges included high levels of social stigma and difficulty finding employment, with 70% reporting significant issues. The study recommends strengthening rehabilitation programs, improving coordination among relevant agencies, conducting anti-stigma campaigns, and simplifying administrative procedures to enhance the reintegration of parolees, ultimately reducing recidivism and benefiting society.